Apigenin is a promising molecule for treatment of visceral leishmaniasis - Emiliano, Yago S. S.; Almeida-Amaral, Elmo E. (Frontiers in Cellular and Infection Microbiology, 2023)
Current treatment for visceral leishmaniasis is based on drugs such as pentavalent antimony and amphotericin B. However, this treatment remains mostly ineffective and expensive, resulting in several side effects and generating resistance. Apigenin, a flavonoid present in fruits and vegetables, has demonstrated several biological functions. In the present study, we observed a concentration-dependent inhibition of the L. infantum promastigote in the presence of apigenin, exhibiting an IC50 value of 29.9 µM. Its effect was also evaluated in L. infantum-infected murine peritoneal macrophages, presenting an C50 value against intracellular amastigotes of 2.3 µM and a selectivity index of 34.3. In a murine model of visceral leishmaniasis, the in vivo effect of apigenin was measured using short-term and long-term treatment schemes. Treatment with apigenin demonstrated 99.7% and 94% reductions in the liver parasite load in the short-term and long-term treatment schemes, respectively. Furthermore, no alterations in serological and hematological parameters were observed. Taken together, these results suggest that apigenin is a potential candidate for visceral leishmaniasis chemotherapy by oral administration.